Constructions and enactments of whiteness: a discursive analysis. (24th August 2012) - Wallis, Jennifer; Singh, Reenee
Abstract : Systemic therapists have argued that it is important to re‐examine issues about white identities if they are to develop cultural competence and cultural sensitivity. Despite this, few studies have explored whiteness in systemic psychotherapy. This small‐scale qualitative study therefore explores how a group of white systemic psychotherapists (trainers and trainees) construct whiteness, how these constructions or discourses facilitate or constrain talk about whiteness and how this influences what therapists do in therapy. The research method used was focus group discussions and an action research approach. The data were analysed using Foucauldian discourse analysis and three main discourses were made apparent: 'whiteness as an invisible norm', 'political correctness' and 'systemic therapy discourses'. These discourses are described and the implications, discussed.